The Study Of Coastal Dike Construction For Jakarta Flood Protection - Hari Suprayogi; Agus Rudyanto; Leo Eliasta; Huda Bachtiar; Midian Wahyu Tukuboya; Lily M. Limantara (JURNAL TEKNIK HIDRAULIK, 2017)
National Capital Integrated Coastal Development Program (here in after called NCICD Program) in Jakartas as National Capital City has main function for flood protection and to countermeasure the land subsidence purposes. According to Bappenas (National Planning Agency), the Updated-Masterplan NCICD program has three phases; 1) Critical-phase 2) Mid-term phase 3) Option-phase. The critical-phase sea dike construction is projected to protect Jakarta until 2030. Land subsidence is the main factor that the ciritical-phase of sea dike must be constructed. Jakarta sinks down with the range of 2-20 cm/ year. Therefore, the existing dike level also becomes lower along the time. Three focus area of sea dike construction under Ministry of Public Works and Housing (here in after called PUPR) are Muara Kamal, Kalibaru, and Muara Baru. At the moment, PUPR concentrates in Kalibaru and Muara Baru with the physical construction progress around 48% from the total length 4.,8 km and it will be finished in 2019. These are essential due to many people live there. The construction of typical sea dike is spoon-pile with shifting construction to the sea between 50 m-100 m from mainland with the crest level +4.8 m from Lowest Water Spring. This type is chosen due to its efficiency on spatial and preventing social conflicts. In addition, the space between the main land and the spoon pile will be nourished by the sand to use it for public infrastructure, such as park. The material behind the dike and the toe protection in front the dike is used for stability purposes, avoid scouring, and reducing wave energy interact the dike itself.